Abstract ID: 125 Fundamental study for practical application of radiotherapy treatment planning system capable of evaluating neutron dose generated by various radiotherapy beams. (October 2017) - Takada, Kenta; Kumada, Hiroaki; Kouketsu, Junichi; Tobita, Syouya; Terunuma, Toshiyuki; Sakurai, Hideyuki; Sakae, Takeji
Abstract : There are many papers focused on secondary neutrons by calculation or measurement in high-energy radiotherapy fields[1, 2] . Monte Carlo calculation is easy to acquire the three-dimensional spatial distribution of the neutrons and is considered to be particularly useful tool for evaluating the "on-axis" of the primary radiotherapy beam. In this study, calculations were performed for practical application of treatment planning that can take three-dimensional neutron dose into account by combining with new treatment planning system "Tsukuba-Plan" currently developed by University of Tsukuba. The incident radiotherapy beams were X-rays and "passive" particle beams (proton beam, carbon-ion beam). Particle and Heavy Ion Transport code System (PHITS)[3] was used as Monte Carlo code. We constructed calculation geometries that reproduces the actual beam delivery systems of these radiotherapy fields as precisely as possible, and confirmed consistency by comparing with measured percentage depth absorbed dose. The neutron doses and energy spectrums of "on-axis" and "off-axis" in homogeneous water phantom were calculated by irradiating each primary beams. Calculated neutron doses were compared with some published literatures. As next step, we used the Tsukuba-Plan to obtain the three-dimensional neutron dose distributions in human-shaped phantom in case of irradiating clinical beams with patient-specific devices such as bolus and collimators. We achieved a relative comparison of the secondary neutron doses and energy spectrums at "on-axis" and "off-axis" of each incident beams by using PHITS code. Additionally, the three-dimensional neutron dose distributions in the human-shaped phantom by each beams were obtained by combining the Tsukuba-Plan. In the future, this function can be used for various evaluation of the secondary neutrons in radiotherapy fields under individualized irradiation conditions.